2017
DOI: 10.1039/c7cp03717a
|View full text |Cite
|
Sign up to set email alerts
|

The properties of residual water molecules in ionic liquids: a comparison between direct and inverse Kirkwood–Buff approaches

Abstract: We study the properties of residual water molecules at different mole fractions in dialkylimidazolium based ionic liquids (ILs), namely 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIM/BF4) and 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM/BF4) by means of atomistic molecular dynamics (MD) simulations. The corresponding Kirkwood-Buff (KB) integrals for the water-ion and ion-ion correlation behavior are calculated by a direct evaluation of the radial distribution functions. The outcomes are compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 121 publications
(137 reference statements)
4
32
0
Order By: Relevance
“…as the standard definition for a Kirkwood-Buff integral. 40,43,44 In accordance with Refs. 43 and 44, Kirkwood-Buff integrals can be interpreted as excess volumes and can be further evaluated in order to estimate the excess number of particles…”
Section: Theoretical Backgroundsupporting
confidence: 89%
See 1 more Smart Citation
“…as the standard definition for a Kirkwood-Buff integral. 40,43,44 In accordance with Refs. 43 and 44, Kirkwood-Buff integrals can be interpreted as excess volumes and can be further evaluated in order to estimate the excess number of particles…”
Section: Theoretical Backgroundsupporting
confidence: 89%
“…The local composition of a PIL system at different length scales can be studied through partial structure factors, which were already established for molecular ionic liquid/water mixtures 24,40 according to the relation 41,42…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The MD simulation studies have shown that more number of water molecules can accommodate around [BMIM][BF 4 ] as compared to the [EMIM][BF 4 ] due to the larger molecular size of the BMIM + cation . This study revealed that the water binding to BMIM cation is more preferable as compared to the EMIM cation . This process governs interactions between the cation possessing alkyl group and the solvents have been described in details by Frank and Evan which fits nicely with the present study.…”
Section: Resultssupporting
confidence: 88%
“…It has also been reported that the [EMIM][BF 4 ] shows higher mass density as compared to the [BMIM][BF 4 ]. The MD simulation studies have shown that more number of water molecules can accommodate around [BMIM][BF 4 ] as compared to the [EMIM][BF 4 ] due to the larger molecular size of the BMIM + cation . This study revealed that the water binding to BMIM cation is more preferable as compared to the EMIM cation .…”
Section: Resultsmentioning
confidence: 85%
“…It is worth noting that KB theory can also be applied to experimental data to evaluate the underlying radial distribution functions via an indirect technique [34,161,162]. A recent study on the convergence of experimental and simulation data for water in ionic liquids reveals the benefits of combined experimental and computational approaches [163].…”
Section: Solubility Of Salts In Presence Of Co-solvent Moleculesmentioning
confidence: 99%